2018
DOI: 10.1021/acs.orglett.8b01370
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Total Synthesis of (−)-(3R)-Inthomycin C

Abstract: A short (10 step) and efficient (15% overall yield) synthesis of the natural product (-)-(3 R)-inthomycin C is reported. The key steps comprise three C-C bond-forming reactions: (i) a vinylogous Mukaiyama aldol, (ii) an olefin cross-metathesis reaction, and (iii) an asymmetric Mukaiyama-Kiyooka aldol. This route is notable for its brevity and has the advantage of lacking stoichiometric tin-promoted cross-coupling reactions present in previous approaches. Initial investigations on the biological activity of (-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Utilizing the same sequence as applied to the synthesis of inthomycin As ((+)-1) and B ((+)-2) from (+)-146a and (+)-146b, respectively (see Scheme 25), the triene (+)-146c was successfully converted into an 8:1 mixture of inthomycin C ((−)-3) and another minor isomer in good overall yield after the final step (Scheme 26). The spectroscopic data and specific rotation values of the three inthomycins A-C ((+)-1, (+)-2, and (−)-3) were consistent with those reported previously [8,23,57]. The absolute configurations of inthomycins A-C ((+)-1, (+)-2, and (−)-3) were reconfirmed as 3R by assigning the (R)-stereochemical descriptor for the common intermediate (−)-140, which supports the recent work of Hale and Hatakeyama [57].…”
Section: Soon After a Subsequent Collaboration Between The Hale Andsupporting
confidence: 91%
See 2 more Smart Citations
“…Utilizing the same sequence as applied to the synthesis of inthomycin As ((+)-1) and B ((+)-2) from (+)-146a and (+)-146b, respectively (see Scheme 25), the triene (+)-146c was successfully converted into an 8:1 mixture of inthomycin C ((−)-3) and another minor isomer in good overall yield after the final step (Scheme 26). The spectroscopic data and specific rotation values of the three inthomycins A-C ((+)-1, (+)-2, and (−)-3) were consistent with those reported previously [8,23,57]. The absolute configurations of inthomycins A-C ((+)-1, (+)-2, and (−)-3) were reconfirmed as 3R by assigning the (R)-stereochemical descriptor for the common intermediate (−)-140, which supports the recent work of Hale and Hatakeyama [57].…”
Section: Soon After a Subsequent Collaboration Between The Hale Andsupporting
confidence: 91%
“…Inthomycins were reported to possess many interesting biological properties, which include the specific inhibition of the cellular biosynthesis [1,4], in vitro antimicrobial activity [4,5], and anticancer activity against human prostate cancer cell lines [6,7]. A recent study suggested that the close analogue (+)-11 of inthomycin C was found to exhibit proteasome inhibition activity [8]. The skeletal structures of inthomycins A-C (1-3) are embodied in several other naturally occurring compounds, such as neooxazolomycin (4), oxazolomycins A-C (5, 6) [9][10][11][12][13][14], curromycins (7) [15], and KSM-2690 (8) [16] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Ryu reported an enantioselective synthesis of inthomycin C 3 which was followed by Hale's reports on the enantioselective synthesis of 3 . Very recently the Donohoe group published an enantioselective synthesis of inthomycin C 3 . All of the syntheses of the inthomycins bar one, feature a Stille cross‐coupling as a key step with the inherent problems associated with the toxicity and disposal of stoichiometric organotin waste.…”
Section: Figurementioning
confidence: 99%
“…We envisaged that inthomycins A-C (1-3), could all be prepared throughc ross-coupling of the (E)-or (Z)-alkenyl iodides 5 with the (E,E)-or (E,Z)-dienylboronic esters 4 ( Figure 2). The dienylboronic esters 4 were to be prepared by syn or anti hydroboration of the enyne oxazole 6 with the enyne oxazole 6 being prepared from alkylation of oxazole 8 with an electrophile derived from commerciallya vailable( E)-pent-2-en-4-yn-1ol (7). The iodides 5 were to be prepared using an enantiose-lectiveK iyooka aldol reaction [14] between the silylketene acetal 9 and the known (E)-or (Z)-iodoaldehydes 10,w hich can be readily prepared from propargyl alcohol 11.T his modular route allowed the ready synthesis of all three inthomycins A-C 1-3.…”
mentioning
confidence: 99%